WORLD AND EUROPEAN EXPERIENCE OF INCLUSIVE DEVELOPMENT MODEL REALIZATION - Lutskiv, Olena (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
The article identifies features of an inclusive model of economic development. Different approaches to determining the essence of an inclusive type of economic development are considered. One of which defines inclusive development as sustainable economic growth, whose main purpose is to reduce poverty and inequality. The second approach defines inclusive development as the process of expanding people’s involvement in GDP creation, ensuring equal opportunities for realizing their human potential regardless of socio-economic conditions, gender, place of residence and ethnic roots. The purpose of the article is to explore the world and European experience of implementing the models of inclusive development, to study and summarize their main benchmarks and indicators. It has been determined that the model of inclusive development is based on the following conditions: the state is obliged to enable every person to fully realize his or her potential; to be an active member of society; receive decent pay for the results of their work; equal access to work results, which implies a uniform and sufficient distribution of work results between employees, entrepreneurs and the state through a balanced amount of wages, income and taxes; accessibility to high quality educational and medical services, etc. The features of the American, European, Chinese and Norwegian models of inclusive development are analyzed. Their main priorities and guidelines for social protection and inclusion are highlighted. Ways to achieve inclusive growth are identified. The analysis of economic growth, poverty, population stratification, social guarantees, social expenditures has been carried out. Therefore, investments in education, solving social, national, cultural, demographic, environmental problems, development of health care, science will contribute to the formation of a new economic structure, which will be based on the principles of inclusiveness.